XRCC1 codon 399Gln polymorphism is associated with radiotherapy-induced acute dermatitis and mucositis in nasopharyngeal carcinoma patients - Li, Haijun (BioMed Central, 2013)
BACKGROUND: To evaluate the association between single nucleotide polymorphisms (SNPs) at the 194 and 399 codons of XRCC1, and the risk of severe acute skin and oral mucosa reactions in nasopharyngeal carcinoma patients in China. METHODS: 114 patients with nasopharyngeal carcinoma were sequentially recruited in this study. Heparinized peripheral blood samples were taken for SNPs analysis before the start of radiation treatment. SNPs in XRCC1 (194Arg/Trp and 399Arg/Gln) gene were analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Dermatitis at upper neck and oral mucositis were clinically recorded according to the Common Terminology Criteria for Adverse Events v.3.0. RESULTS: The variant allele frequencies were 0.289 for XRCC1 194Trp and 0.263 for XRCC1 399Gln. Of the 114 patients, 24 experienced grade 3 acute dermatitis and 48 had grade 3 acute mucositis. The XRCC1 399Arg/Gln was significantly associated with the development of grade 3 dermatitis (Odds Ratio, 2.65; 95% CI, 1.04–6.73; p = 0.037, χ2 = 4.357). In addition, it was also associated with higher incidence of grade 3 mucositis with a borderline statistical significance (Odds Ratio, 2.11; 95% CI, 0.951–4.66; p = 0.065, χ2 = 3.411). The relationship between XRCC1 194Arg/Trp and acute dermatitis, and mucositis was not found. CONCLUSIONS: Our investigation shows, for the first time, that patients with the XRCC1 399Arg/Gln genotype were more likely to experience severe acute dermatitis and oral mucositis. With further validation, the information can be used to determine personalized radiotherapy strategy.